Conducting Polymers for Wearable Sensors: A Bibliometric Analysis Using VOSviewer - Mora, Abraham; Aziz, Arrizal Abdul (Universitas Pendidikan Mandalika, 2024)
The objective of this study is to conduct a bibliometric analysis using VOSviewer on the research progress of the conducting polymer for wearable sensors topic. Data was extracted from the Dimensions database from 2014 to August 2023. 268 Dimensions articles were relevant to the keywords. The title and abstract from the metadata were employed to be analyzed for co-occurrence using VOSviewer. As a result, 9544 terms were obtained through the search method, but only 184 met the threshold of 10 minimum occurrences in all retrieved articles and were selected for further analysis. There was a consistent upward trend in publication numbers between 2014 to August 2023. Based on the network visualization of keyword co-occurrence, it evidenced six clusters that group all specific keywords based on the common themes. The most recent keywords (occurred between 2021 and 2022) included conductive hydrogel, polymer hydrogel, flexible sensor, MXene, strain sensor, and stretchable strain sensor. Based on this study, it is suggested to discover more about conducting and flexible hydrogel materials and the possibilities to enhance the electrical and mechanical properties of conducting polymers by introducing MXene. The materials are viewed for applications such as flexible strain sensors and other wearable sensors.